Local health department workers, public policy, and willingness to respond during emergencies - Rutkow, JD, PhD, MPH, Lainie; Vernick, JD, MPH, Jon S.; Thompson, MS, MBA, Carol B.; Hudson, MSN, Robert; Barnett, MD, MPH, Daniel J. (American Journal of Disaster Medicine, 2015)
Objectives: To determine whether an association exists between a state's authority to declare a public health emergency and local public health workers’ response willingness. Design: The 2009-2010 Johns Hopkins~Public Health Infrastructure Response Survey Tool included questions about demographics and attitudes/beliefs regarding local public health workers’ response willingness during public health emergencies. Survey data were merged with data about presence/absence of a law granting states the authority to declare a public health emergency. Logistic regression analyses were performed with the presence/absence of the law and were adjusted for individuals’ demographic and locale characteristics. Setting: Data were collected from eight clusters of local health department workers in nine states. Participants: Two thousand nine hundred ninety-three local health department workers. Main outcome measure: Willingness to respond to four different public health emergency scenarios. Results: For naturally occurring and human-caused disasters, in unadjusted analyses, there was no statistically significant difference in willingness to respond between individuals living in states with a law that allowed for a governmental declaration of public health emergency and those living in states without such a law. Adjusted analyses yielded similar results. Conclusions: While laws giving the state the authority to declare a public health emergency are not associated with response willingness, findings may reflect the fact that states rarely declare public health emergencies, giving local public health workers few opportunities to become familiar with the implementation of these laws. In light of this, local health departments should consider altering their own internal policies to promote response willingness among their employees.